Water Resistant Composite Membranes for Carbon Dioxide Separation from Methane - Colin A. Scholes (Applied Sciences, 2018)
Membranes that are resistant to water vapor permeation have potential in natural gas sweetening by reducing the need for pretreatment. The perfluorinated polymer Teflon AF1600 has proven resistance to water vapor, which is adapted here in the form of composite membranes consisting of a Teflon AF1600 protective layer on membranes of the polyimide 4,4′-(hexafluoroisopropylidene) diphthalic anhydride 2,3,5,6-tetramethyl-1,4-phenylenediamine (6FDA-TMPDA) as well as Polymer of Intrinsic Micro-porosity (PIM-1). The permeability of CO2 and CH4 through the composite membranes was shown to be a function of the respective permeabilities of the individual polymer layers, with the Teflon AF1600 layer providing the majority of the resistance to mass transfer. Upon exposure to water, the composite membranes had reduced water permeation of 7–13% compared to pure membranes of 6FDA-TMPDA and PIM-1, because of the water resistance of the Teflon AF1600 layer. It was observed that water permeated as clusters through the composite structure. Under CO2-CH4 mixed gas conditions, 6FDA-TMPDA layer permselectivity performance was reduced and became comparable to Teflon AF1600, while the PIM-1 layer retained much of its high permselectivity performance. Importantly, at water activities below 0.2 the PIM-1 composite membrane achieved higher permeability for CO2 compared to water.